2017
DOI: 10.3389/fmicb.2017.01315
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 2 Is a Component of Influenza A Virus-Induced Host Antiviral Response

Abstract: Host cells produce variety of antiviral factors that create an antiviral state and target various stages of influenza A virus (IAV) life cycle to inhibit infection. However, IAV has evolved various strategies to antagonize those antiviral factors. Recently, we reported that a member of class I host histone deacetylases (HDACs), HDAC1 possesses an anti-IAV function. Herein, we provide evidence that HDAC2, another class I member and closely related to HDAC1 in structure and function, also possesses anti-IAV prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 72 publications
9
35
0
Order By: Relevance
“…However, only Class I and Class II HDACs have been shown to be implicated in this phenomenon (Carlomagno et al, ; Krämer & Heinzel, ; Yan et al, ). In agreement with this, we earlier showed that IAV‐induced phosphorylation of STAT1 is downregulated in HDAC inhibitor‐treated (Nagesh & Husain, ) or HDAC2‐depleted cells (Nagesh et al, ). Likewise, as shown herein, the IAV‐induced (as well as IFNα‐induced) phosphorylation of STAT1 is also downregulated in HDAC11‐depleted cells.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…However, only Class I and Class II HDACs have been shown to be implicated in this phenomenon (Carlomagno et al, ; Krämer & Heinzel, ; Yan et al, ). In agreement with this, we earlier showed that IAV‐induced phosphorylation of STAT1 is downregulated in HDAC inhibitor‐treated (Nagesh & Husain, ) or HDAC2‐depleted cells (Nagesh et al, ). Likewise, as shown herein, the IAV‐induced (as well as IFNα‐induced) phosphorylation of STAT1 is also downregulated in HDAC11‐depleted cells.…”
Section: Discussionsupporting
confidence: 81%
“…This indicates that HDAC11 siRNA does contribute to further reducing the HDAC11 mRNA level during the course of infection and, consequently, to IAV proliferation. The extent of increase in virus release from HDAC11‐depleted cells was larger than about 3.0‐, 4.0‐, and 6.0‐fold increase from HDAC 1‐, 2‐, and 6‐depleted cells, respectively, we observed earlier (Husain & Cheung, ; Nagesh et al, ; Nagesh & Husain, ). One of the possible explanations for this could be that, compared with the Classes I and II HDACs, HDAC11 is evolutionarily the least evolved HDAC and has retained the original structure as well as function assigned to its common ancestral gene(s) by nature.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations